Mechanical Behavior for Polymer Matrix Composite Reinforced By Copper Powder - Mohammed, Mohammed Abdulsattar (Nahrain University College of Engineering Journal, 2011)
The mechanical properties of commercial epoxide resin type conipox 77Z have been investigated both unfilled and filled with varying weight fraction of copper particles. The values of Young s modulus, modulus of rigidity, yield stress, tensile strength, shear strength, flexural strength, fracture energy, impact strength, coefficient of friction and the S/N curves and the fatigue strength or fatigue limit have been studied at room temperature (25°C) to a certain the influence of weight fraction of copper powder to epoxy resin (0%, 5%, 10% and 15%) and found that increasing the weight fraction of copper powder to epoxy fordifferent particle sizes leads to an increase in modulus of elasticity (E), modulus of rigidity (G), tensile yield stress and ultimate tensile strengthbut at the same time will decrease the compression yield stress, fracture energy and the impact strength. Finally the reinforced epoxy with (15%) wasfound to be improving the mechanical properties for composite material, where the modulus of elasticity and the modulus of rigidity increasedand the coefficient of friction of the composite material to steel decreased.